Pengaruh Penggunaan Artificial Intelligence dalam Personalisasi Iklan terhadap Kepuasan Pelanggan - Ibrahim, Darmawansah (Jurnal Ilmiah Manajemen & Kewirausahaan, 2024)
This study aims to analyze the effect of Artificial Intelligence (AI) usage in ad personalization on customer satisfaction. AI-based ad personalization enables companies to tailor advertising content according to individual behavior, preferences, and characteristics, thereby increasing the relevance and effectiveness of marketing communication. The study employs a quantitative approach using surveys to collect data. Questionnaires were distributed to consumers who received AI-personalized digital advertisements. The results indicate that the implementation of AI in ad personalization has a positive and significant effect on customer satisfaction. Consumers perceive their interactions with advertisements as more relevant, engaging, and aligned with their needs, which enhances their positive perception of the brand and overall satisfaction.